Pengaruh Pertumbuhan Ekonomi Dan IPM Terhadap Tingkat Kemiskinan Di Kabupaten Pasuruan - Risa Wulandari; lucky Rachmawati (Universitas Negeri Surabaya, 2021)
The purpose of this article is to identify the effect of economic growth and HDI (Human Development Index) on poverty levels in Pasuruan Regency in the 2012-2020 period. Quantitative descriptive with lag distribution model technique is the type of research used. This data is from secondary data, namely the Central Statistics Agency (BPS) with a period of 9 years, namely 2012-2020. In this process using the time series data method assisted by the SPSS 25 software tool. The results of the regression test of the research resulted in, among others 1). Economic growth partially has no effect on the poverty level in the Pasuruan Regency. 2). The HDI has a negative effect on the poverty level, meaning that every increase in the HDI will increase the poverty level in the Pasuruan Regency. 3). Economic growth and HDI have a simultaneous effect on the level of poverty in the Pasuruan Regency. 4). The value of the coefficient of determination of 0.885 indicates the effect of economic growth and HDI simultaneously F of 88.5% on the poverty level in the Pasuruan Regency and 11.5% less due to the influence of not variables in the regression but outside the regression model.